The improvement of train formation interaction on technical stations with train schedule - Стахорний, Дмитро Борисович; Малахова, Олена Анатоліївна (Technology audit and production reserves, 2014)
It is shown that one of the measures to ensure the effectiveness and reliability of the schedule is use of flexible weighted norms. As a result of working conditions research of railway yards at sending of trains using flexible standards of weight and length of train will be found that flexible train formation management will reduce the interoperable down time, including downtime of trains awaiting departure at 60-80%. Irregularity reducing favorably affects both their performance and the performance of those companies that it serves. Therefore, in order to keep the constant movement size on the assumption of uniform departure of trains is advisable to reduce the minimum, or increase the maximum norm. Implementation of freight trains movement technology according to schedule is better starting with sites and directions with stable train flows.